Search for contact interactions in e±p collisions at HERA - Aaron, Francisc Dionisie; Pirumov, Hayk; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (Physics letters, 2011)
A search for physics beyond the Standard Model in neutral current deep inelastic scattering at high negative four-momentum transfer squared Q2 is performed in e±p collisions at HERA. The differential cross section dσ/dQ2, measured using the full H1 data sample corresponding to an integrated luminosity of 446 pb−1, is compared to the Standard Model prediction. No significant deviation is observed. Limits on various models predicting new phenomena at high Q2 are derived. For general four-fermion eeqq contact interaction models, lower limits on the compositeness scale Λ are set in the range 3.6 TeV to 7.2 TeV. Leptoquarks with masses MLQ and couplings λ are constrained to MLQ/λ>0.41-1.86 TeV and limits on squarks in R-parity violating supersymmetric models are derived. A lower limit on the gravitational scale in 4+n dimensions of MS>0.9 TeV is established for low-scale quantum gravity effects in models with large extra dimensions. For the light quark radius an upper bound of Rq<0.65⋅10−18 m is determined.